The scriptural tale in the fourth gospel : with particular reference to the prologue and a syncretic (oral and written) poetics - Gerber, Edward H. (Biblical interpretation series,, 2016)
A more nuanced view of the Fourth Gospel's media nature suggests a new and promising paradigm for assessing expansive and embedded uses of scripture in this work. The majority of studies exploring the Fourth Evangelist's use of scripture to date have approached the Fourth Gospel as the product of a highly gifted writer, who carefully interweaves various elements and figures from scripture into the canvas of his completed document. The present study attempts to calibrate a literary approach to the Fourth Gospel's use of scripture with an appreciation for oral poetic influences, whereby an orally-situated composer's use of traditional references and compositional strategy could be of one and the same piece. Most importantly, pre-formed story-patterns - thick with referential meaning - were used in the construction of new works. The present study makes the case that the Fourth Evangelist has patterned his story of Jesus after a retelling of the story of Adam & Israel in two interrelated ways: first in the prologue, and then in the body of the Gospel as a whole.